2017
DOI: 10.7448/ias.20.01/21372
|View full text |Cite
|
Sign up to set email alerts
|

Community engagement in sexual health and uptake of HIV testing and syphilis testing among MSM in China: a cross‐sectional online survey

Abstract: Introduction: HIV and syphilis testing rates remain low among men who have sex with men (MSM) in low- and middle-income countries (LMICs). Community engagement has been increasingly used to promote HIV testing among key populations in high-income countries, often in settings with stronger civil society. This study aimed to assess socio-demographic, behavioural, and community engagement factors associated with HIV and syphilis testing among MSM in China.Methods: MSM ≥16 years old who had condomless sex in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 53 publications
6
50
0
Order By: Relevance
“…This is consistent with previous studies that found community engagement in sexual health to be associated with increased HIV testing and syphilis testing [35]. This suggests that influencers could be helpful in promoting dual HIV/syphilis testing, given that these related infections often co-occur among MSM in China [39].…”
supporting
confidence: 81%
See 1 more Smart Citation
“…This is consistent with previous studies that found community engagement in sexual health to be associated with increased HIV testing and syphilis testing [35]. This suggests that influencers could be helpful in promoting dual HIV/syphilis testing, given that these related infections often co-occur among MSM in China [39].…”
supporting
confidence: 81%
“…After adjusting for the intervention, influencers in our study also had a higher likelihood of HIV testing. Their higher HIV testing may be related to increased community engagement in sexual health [35] and HIV testing-related social media use. [37] The higher rates of HIV testing among influencers may also be related to lower HIV stigma and higher testing self-efficacy which are two important contributors to test uptake [32,38].…”
mentioning
confidence: 99%
“…Formal mechanisms to solicit feedback from patients, members of the LGBTQ community, and persons of rural background in the city and countryside should be considered as part of intervention design. Community participatory methods such as crowdsourcing may also be helpful for soliciting community feedback . Second, our findings underscore the urgent need for interventions to address structural barriers to sexual health services, such as lack of HIV/STD awareness among rural transplant MSM or institutional stigma in healthcare settings, beyond just those seeking to affect individual behaviours of rural transplant community.…”
Section: Discussionmentioning
confidence: 80%
“…There may be ascertainment bias where the report of dual testing may be systematically underestimated if men who received HIV testing were not told they were also tested for syphilis by the testing provider. Triangulating self-reported data with clinic databases would increase the accuracy of our findings but this was not practical, and other studies have similarly used self-reports to estimate syphilis testing in MSM 10. While our study focused on patient factors, an important area for future research would be to further explore physician factors for offering a single HIV test compared with dual testing.…”
Section: Discussionmentioning
confidence: 99%